Unsteady hydrodynamic forces acting on a robotic arm and its flow field: Application to the crawl stroke - Takagi, H.; Nakashima, M.; Ozaki, T.; Matsuuchi, K. (Journal of Biomechanics, 2014)
This study aims to clarify the mechanisms by which unsteady hydrodynamic forces act on the hand of a swimmer during a crawl stroke. Measurements were performed for a hand attached to a robotic arm with five degrees of freedom independently controlled by a computer. The computer was programmed so the hand and arm mimicked a human performing the stroke. We directly measured forces on the hand and pressure distributions around it at 200 Hz; flow fields underwater near the hand were obtained via 2D particle image velocimetry (PIV). The data revealed two mechanisms that generate unsteady forces during a crawl stroke. One is the unsteady lift force generated when hand movement changes direction during the stroke, leading to vortex shedding and bound vortex created around it. This bound vortex circulation results in a lift that contributes to the thrust. The other occurs when the hand moves linearly with a large angle of attack, creating a Kármán vortex street. This street alternatively sheds clockwise and counterclockwise vortices, resulting in a quasi-steady drag contributing to the thrust. We presume that professional swimmers benefit from both mechanisms. Further studies are necessary in which 3D flow fields are measured using a 3D PIV system and a human swimmer.